Evaluating Consensus Among Physicians in Medical Knowledge Base Construction - Giuse, N. B.; Giuse, D. A.; MMer, R. A.; Bankowitz, R. A.; Janosky, J. E.; Davidoff, F.; Hillner, B. E.; Hripcsak, G.; Lincoln, M. J.; Middleton, B.; Peden, J. G., Jr. (Methods of Information in Medicine, 1993)
This study evaluates inter-author variability in knowledge base construction. Seven board-certified internists independently profiled “acute perinephric abscess”, using as reference material a set of 109 peer-reviewed articles. Each participant created a list of findings associated with the disease, estimated the predictive value and sensitivity of each finding, and assessed the pertinence of each article for making each judgment. Agreement in finding selection was significantly different from chance: seven, six, and five participants selected the same finding 78.6, 9.8, and 1.6 times more often than predicted by chance. Findings with the highest sensitivity were most likely to be included by all participants. The selection of supporting evidence from the medical literature was significantly related to each physician’s agreement with the majority. The study shows that, with appropriate guidance, physicians can reproducibly extract information from the medical literature, and thus established a foundation for multi-author knowledge base construction.
Keywords: Medical Knowledge Bases; Knowledge Acquisition; Medical Informatics Applications; Expert Systems; Data Interpretation; Statistical